2015
DOI: 10.4103/0300-1652.171616
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of some cardiovascular risk factors in predialysis chronic kidney disease patients in Southern Nigeria

Abstract: Background:Cardiovascular risk factors are responsible for cardiovascular disease and rapid progression of chronic kidney disease (CKD) to end-stage renal disease. Prompt evaluation, modification, and treatment of these factors in predialysis patients will reduce morbidity and mortality. This study assessed some cardiovascular risk factors in predialysis CKD patients in a tertiary hospital in Southern Nigeria.Patients and Methods:This was a case–control study that involved 76 consecutive predialysis CKD patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 29 publications
4
8
4
Order By: Relevance
“…Hyperuricemia is also considered to be a risk factor for CVD events and all-cause mortality. 21 The prevalence of hyperuricemia in present study (71%) is much higher than reported prevalence of 57.9% in pre-dialysis CKD patients by Adejumo et al 31 and there is no significant difference in hyperuricemia among the stages of CKD in both the studies. Studies have shown that the risk of CVD events and all-cause mortality increases by about 10% with every mg/dl rise in uric acid.…”
Section: Resultscontrasting
confidence: 57%
See 3 more Smart Citations
“…Hyperuricemia is also considered to be a risk factor for CVD events and all-cause mortality. 21 The prevalence of hyperuricemia in present study (71%) is much higher than reported prevalence of 57.9% in pre-dialysis CKD patients by Adejumo et al 31 and there is no significant difference in hyperuricemia among the stages of CKD in both the studies. Studies have shown that the risk of CVD events and all-cause mortality increases by about 10% with every mg/dl rise in uric acid.…”
Section: Resultscontrasting
confidence: 57%
“…39 Significant reduction of serum albumin from stage 3 to 5 predialysis CKD patients observed in present study (p<0.03) is similar to other studies in abroad 9 and in Nepal. 12 However, hypoalbuminemia, a marker of malnutrition, found in 93% of our study population with no difference between the CKD stages contradicts the prevalence of 35.5% reported from Nigeria by Adejumo et al 31 with significant increase of hypoalbuminemia from CKD stage 3 to stage 5.…”
Section: Resultssupporting
confidence: 45%
See 2 more Smart Citations
“…It was observed from previous studies that approximately two-thirds of uric acid in the human body is excreted by the kidneys, and one-third is excreted by intestinal microorganisms following degradation (24)(25)(26)(27)(28). due to the limited water-solubility of uric acid, increasing the level of uric acid excretion in the kidneys will increase the burden on the organ and lead to renal diseases (29,30). Furthermore, recombinant uricase has been used to convert uric acid into allantoin in the human body in order to decrease the levels of uric acid, but its clinical application is limited due to its side effects, including immunogenicity of heterologous proteins (31,32).…”
Section: Introductionmentioning
confidence: 99%